1963
DOI: 10.2134/agronj1963.00021962005500030007x
|View full text |Cite
|
Sign up to set email alerts
|

Residual Nitrogen from NH4NO3 Fertilizer and from Alfalfa Plowed under1

Abstract: Synopsis Residual N from NH4NO3 averaged 44% of the original application after 1 year but was insignificant after 2 years. For a 5‐year period, N uptake from the alfalfa area exceeded that from virgin area by 341 pounds per acre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
1

Year Published

1970
1970
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 2 publications
2
10
1
Order By: Relevance
“…Other research showed that the nitrate-N in mineralization bags estimated the N available to potato (Solanum tuberosum L.) and corn during the growing season (Westermann and Crothers, 1980). Several studies demonstrated that fertilizer N may not be required following a legume crop (Boawn et al, 1963;Fox and Piekielek, 1988). The N fertilizer requirement depends on (i) how well the N mineralization pattern synchronizes with the crop's N uptake pattern, and (ii) whether sufficient N has mineralized to satisfy the rapid N uptake requirement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other research showed that the nitrate-N in mineralization bags estimated the N available to potato (Solanum tuberosum L.) and corn during the growing season (Westermann and Crothers, 1980). Several studies demonstrated that fertilizer N may not be required following a legume crop (Boawn et al, 1963;Fox and Piekielek, 1988). The N fertilizer requirement depends on (i) how well the N mineralization pattern synchronizes with the crop's N uptake pattern, and (ii) whether sufficient N has mineralized to satisfy the rapid N uptake requirement.…”
Section: Resultsmentioning
confidence: 99%
“…6:404-408 (1993). residues can also contribute significant amounts of N for crop use over time. Nitrogen uptake by corn over five cropping years from an area previously in alfalfa was 341 lb/acre greater than that from an uncropped soil area (Boawn et al, 1963). Crop sequence after legumes can also have a significant role in capturing the N mineralized.…”
Section: Researchmentioning
confidence: 94%
“…Alfalfa (Medicago sativa L.) removes water and NO,-N from deeper in the soil profile than other crops (2,7,11), and is an excellent NO 3 scavenger for reducing the amount of NO3-N leaching following a high N fertilized crop, or where alfalfa crops have received excessive N fertilizer applications (7). This characteristic has been utilized in renovating high N waste waters.…”
Section: Introductionmentioning
confidence: 99%
“…The high NO3-N levels found in some areas may come from any of several sources, and the sources must be idenified if management practices are to be changed to reduce nonpoint NO,-N sources entering subsurface, and eventually, surface waters. Nitrate leaching rates are a function of irrigation and precipitation rate and timing, nitrogen fertilizer application rate and timing (1, 6), and the crops grown (9, 12).Alfalfa (Medicago sativa L.) removes water and NO,-N from deeper in the soil profile than other crops (2,7,11), and is an excellent NO 3 scavenger for reducing the amount of NO3-N leaching following a high N fertilized crop, or where alfalfa crops have received excessive N fertilizer applications (7). This characteristic has been utilized in renovating high N waste waters.…”
mentioning
confidence: 99%
“…Contributions made by alfalfa to the soil N supply have long been recognized (Lyon and Bizzell 1933;Boawn et al 1963;Hoyt and Hennig 1971;Campbell et al 1993). However, poor synchrony between N release from legume residues and crop N demands may reduce the fertility benefits of the legume (Huntington et al 1985;Westermann and Crothers 1993).…”
mentioning
confidence: 99%